Newly Discovered Triassic Lithium Deposits in the Dahongliutan Area, NorthWest China: A Case Study for the Detection of Lithium-Bearing Pegmatite Deposits in Rugged Terrains Using Remote-Sensing Data and Images - Gao, Yongbao; Bagas, Leon; Li, Kan; Jin, Moushun; Liu, Yuegao; Teng, Jiaxin (Frontiers in Earth Science, 2020)
Rare metals, such as lithium and cobalt used in rechargeable batteries, have increased in value as demands for them escalates. Concentrations of lithium-bearing minerals are found in closed-basin brines, granitic pegmatites, and associated granitic rocks containing spodumene (LiAl(SiO3)2) and various other economic minerals. The recently discovered Dahongliutan Li mineral occurrences are hosted by a pegmatite dyke swarm in NW China, in an area that is also prospective for Be, Rb, Nb, and Ta mineralisation. However, the high altitude and steep topography in the area make it extremely difficult to explore for mineralisation. A combination of geochemical methods, geological mapping, and high-resolution remotely sensed multispectral imagery has been used in this study to pinpoint potential locations of pegmatite-hosted Li occurrences. The exploration method developed has led to the discovery many large Li mineral occurrences in the Bayankala Fold Belt, including the 505, 507, north 509, and South Fulugou 1# and 2# mineral occurrences (documented here) with a combined resource of over 1.7 million tonnes (Mt). The laser ablation multi-receiver inductively coupled plasma mass spectrometer (LA-MC-ICP-MS) 206Pb/207Pb-238U/207Pb isochron age of the mineralised pegmatite is 223 ± 11 Ma (N = 44, MSWD = 2.1). The 40Ar/39Ar plateau age of muscovite in the mineralised pegmatite dates between 197 ± 1 and 185 ± 1 Ma. These dates show that these granitic pegmatites (with a monzogranitic composition) were emplaced during the Late Triassic coeval with magmatism in the region. Our data show that the Li mineralisation in the Dahongliutan area has a similar age and genesis as the pegmatite-hosted deposits of the Jiajika area in the western Sichuan Province. This indicates that the Dahongliutan area is highly prospective of various pegmatite-hosted mineral deposits.